Advance Demand Information, Price Discrimination, and Preorder Strategies - Li, Cuihong; Zhang, Fuqiang (Manufacturing and Service Operations Management, 2013)
This paper studies the preorder strategy that a seller may use to sell a perishable product in an uncertain market with heterogeneous consumers. By accepting preorders, the seller is able to obtain advance demand information for inventory planning and price discriminate the consumers. Given the preorder option, the consumers react strategically by optimizing the timing of purchase. We find that accurate demand information may improve the availability of the product, which undermines the seller's ability to charge a high preorder price. As a result, advance demand information may hurt the seller's profit due to its negative impact for the preorder season. This cautions the seller about a potential conflict between the benefits of advance demand information and price discrimination when facing strategic consumers. A common practice to contain consumers' strategic waiting is to offer price guarantees that compensate preorder consumers in case of a later price cut. Under price guarantees, the seller will reduce price in the regular season only if the preorder demand is low; however, such advance information implies weak demand in the regular season as well. This means that the seller can no longer benefit from a high demand in the regular season. Therefore, under price guarantees, more accurate advance demand information may still hurt the seller's profit due to its adverse impact for the regular season. We also investigate the seller's strategy choice in such a setting (i.e., whether the preorder option should be offered and whether it should be coupled with price guarantees) and find that the answer depends on the relative sizes of the heterogeneous consumer segments.